2022
DOI: 10.1149/1945-7111/ac62c6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Redox Shuttle Generation in LFP/Graphite and NMC811/Graphite Cells

Abstract: Unwanted redox shuttles can lead to self-discharge and inefficiency in lithium-ion cells. This study investigates the generation of a redox shuttle in LFP/graphite and NMC811/graphite pouch cells with common alkyl carbonate electrolyte. Visual inspection of the electrolyte extracted after formation at temperatures between 25 and 70°C reveals strong discoloration. Such extracted electrolytes with intense red and brown color show relatively large shuttling currents in Al/Li coin cells. Two weight percent of viny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 34 publications
5
69
0
Order By: Relevance
“…The associated mechanical degradation in the form of particle disintegration and the resulting greater exposure of active material to the electrolyte may also enhance the TM dissolution rate. Ni deposition on the anode due to cathode cross-talk has been shown to result in accelerated SEI growth/thickening that correlates with increased impedance and has been implicated as a main contributor to capacity fade, particularly when charging to high voltages. , , For example, previous work has shown that charging NMC622 cathodes above 4.7 V results in >2× increase in Ni deposits compared to when charging to 4.3 V . The results presented herein suggest that by cycling the cathode at a voltage below the H2 ⇄ H3 transition, high levels of Ni deposits on the negative electrode can be avoided.…”
Section: Discussionmentioning
confidence: 68%
“…The associated mechanical degradation in the form of particle disintegration and the resulting greater exposure of active material to the electrolyte may also enhance the TM dissolution rate. Ni deposition on the anode due to cathode cross-talk has been shown to result in accelerated SEI growth/thickening that correlates with increased impedance and has been implicated as a main contributor to capacity fade, particularly when charging to high voltages. , , For example, previous work has shown that charging NMC622 cathodes above 4.7 V results in >2× increase in Ni deposits compared to when charging to 4.3 V . The results presented herein suggest that by cycling the cathode at a voltage below the H2 ⇄ H3 transition, high levels of Ni deposits on the negative electrode can be avoided.…”
Section: Discussionmentioning
confidence: 68%
“…Among cross-talking degradations, chemical shuttling of soluble species was reported for graphite/NMC cell chemistries, for instance when using TFSI-containing electrolytes 31 , but also for Na-ion cells 32 . Species shuttling were found to be lithium (or sodium) alkyl-carbonate 31,32 , alkoxide or organophosphate 33 , as revealed by various characterization methods such calorimetry 34 , high performance liquid chromatography (HPLC) 33 or mass spectrometry (MS) 35 . The first electrochemical indication of shuttling is a decrease of coulombic efficiency (CE) 35 .…”
Section: Loss Of Lithium Inventory (Lli)mentioning
confidence: 99%
“…However, in such case, caution must be exercised when ascribing the observed electrochemical behaviors to shuttling since side reactions at the negative electrode prevails and can hide shuttling current. To complement this electrochemical analysis based on cycling data, further characterizations are thus encouraged to establish the nature of the shuttling species and their reactivity using cyclic voltammetry 31 or ultraviolet visible spectroscopy (UV-VIS) 32 , for instance. In definitive, marching rates is the analysis of choice to closely monitored cell aging and detect early signs of shuttling, which is of prime importance when studying novel electrolyte compositions or investigating the stability of layered compounds at high potentials.…”
Section: Benign Shuttlingmentioning
confidence: 99%
“…An important caveat is that altering the cathode could disrupt other processes relevant to the full-cells of interest, such as crosstalk interactions and redox shuttles. 15,16 Another way to achieve more direct insights about SEI passivation from experiments is by changing the test conditions. The voltage profile of many Si-based materials tends to become steeper a very low Li + content (at potentials above ~1 V vs. Li/Li + , see Figure 1).…”
Section: Practical Considerationsmentioning
confidence: 99%